Synthesis of 3-(5H-Pyrazolyl)cyclobutanone Derivatives - Fu, Pengfei; Li, Zeqing; Wang, Yuqiang; Yu, Pei (Asian Journal of Chemistry, 2015)
A 3-(5H-pyrazolyl)-cyclobutanone derivative was synthesized via two different optimized routes. In the first route, the substitutional pyrazole olefins was prepared as a precursor, the target molecule was synthesized via [2 + 2]-cycloaddition by using pyrazols olefins and ketene in total yield of 3 %. In the second route, the four-member ring cyclobutanone fragment was made first, then the pyrazole ring was obtained through cyclization, offering the target molecule with a yield of 8.6 %.